A Comparative Study on the Development of Islamic Banking in Indonesia and Malaysia from a Regulatory Perspective (Sharia Faculty Islamic Economic Law Study Department, 2025)
Islamic banking has witnessed remarkable expansion on a global scale; however, significant variations persist in its development across different nations. As two of the largest Muslim-majority countries, Indonesia and Malaysia have made continuous strides in advancing their Islamic banking sectors, yet they display notable differences in regulatory structures, market maturity, and institutional strategies. Despite these disparities, the underlying factors driving them and their broader implications for industry growth remain insufficiently examined. This study seeks to bridge this gap through a comprehensive comparative socio-legal analysis of Islamic banking regulations in Indonesia and Malaysia, exploring the extent to which legal frameworks and regulatory policies shape sectoral progress. Indonesia, Malaysia, exploring the extent to which legal frameworks and regulatory policies shape sectoral progress. Utilizing a qualitative, comparative socio-legal methodology, the research examines key legal instruments, including laws, regulations, and guidelines, while also considering socio-economic and institutional dynamics that influence regulatory implementation. The findings reveal that Malaysia’s proactive regulatory framework, introduced even before its first Islamic bank commenced operations in 1983, has contributed to legal certainty, bolstered market confidence, and accelerated institutional development. Conversely, Indonesia implemented its Islamic banking regulations 16 years after the establishment of its first Islamic bank, resulting in a slower pace of market penetration, financial product diversification, and public awareness. This difference has contributed to the varying growth rates and development of Islamic banking in the two countries. Study underscores the pivotal role of early regulatory intervention in cultivating a robust and competitive Islamic banking landscape. By drawing comparisons between Indonesia and Malaysia, the research offers valuable insights for policymakers and financial regulators striving to enhance the global Islamic banking sector. Strengthening legal frameworks and promoting public awareness are fundamental strategies for driving industry growth and ensuring its long-term sustainability.